Answer:
<u>ln(56 + -1z) = 0</u>
Step-by-step explanation:
Simplifying
ln(63) = ln(z) + ln(7)
Reorder the terms for easier multiplication:
63ln = ln(z) + ln(7)
Multiply ln * z
63ln = lnz + ln(7)
Reorder the terms for easier multiplication:
63ln = lnz + 7ln
Reorder the terms:
63ln = 7ln + lnz
Solving
63ln = 7ln + lnz
Solving for variable 'l'.
Move all terms containing l to the left, all other terms to the right.
Add '-7ln' to each side of the equation.
63ln + -7ln = 7ln + -7ln + lnz
Combine like terms: 63ln + -7ln = 56ln
56ln = 7ln + -7ln + lnz
Combine like terms: 7ln + -7ln = 0
56ln = 0 + lnz
56ln = lnz
Add '-1lnz' to each side of the equation.
56ln + -1lnz = lnz + -1lnz
Combine like terms: lnz + -1lnz = 0
56ln + -1lnz = 0
Factor out the Greatest Common Factor (GCF), 'ln'.
<u>ln(56 + -1z) = 0</u>
Could be wrong. If it is, let me know. Thanks! Have a good rest of your day! :)